2022
DOI: 10.3389/fimmu.2022.1039929
|View full text |Cite
|
Sign up to set email alerts
|

Multiple CAR-T cell therapy for acute B-cell lymphoblastic leukemia after hematopoietic stem cell transplantation: A case report

Abstract: B-cell acute lymphoblastic leukemia (B-ALL) is the most common childhood malignancy. The cure rate has reached 90% after conventional chemotherapy and hematopoietic stem cell transplantation (HSCT), but the prognosis of patients with relapsed and refractory (R/R) leukemia is still poor after conventional treatment. Since FDA approved CD19 CAR-T cell (Kymriah) for the treatment of R/R B-ALL, increasing studies have been conducted on CAR-T cells for R/R ALL. Herein, we report the treatment of a patient with ALL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 60 publications
(70 reference statements)
0
1
0
Order By: Relevance
“…CARs are genetically engineered synthetic antigen receptors that are able to activate upon antigen recognition, independent of MHC presentation (24,25). CAR T cell therapy has achieved unprecedented success in treating patients with hematopoietic malignancies, such as acute B-cell lymphoblastic leukaemia and B-cell lymphomas (23,(26)(27)(28). However, only a few studies have shown promise for CAR T cell therapy in solid tumors, such as GD2-CAR T cells for relapsed and refractory Neuroblastoma tumors (29), as well as B7H3-, GD2-and IL13RA2-CAR T cells for human Glioma (30)(31)(32).…”
Section: Introductionmentioning
confidence: 99%
“…CARs are genetically engineered synthetic antigen receptors that are able to activate upon antigen recognition, independent of MHC presentation (24,25). CAR T cell therapy has achieved unprecedented success in treating patients with hematopoietic malignancies, such as acute B-cell lymphoblastic leukaemia and B-cell lymphomas (23,(26)(27)(28). However, only a few studies have shown promise for CAR T cell therapy in solid tumors, such as GD2-CAR T cells for relapsed and refractory Neuroblastoma tumors (29), as well as B7H3-, GD2-and IL13RA2-CAR T cells for human Glioma (30)(31)(32).…”
Section: Introductionmentioning
confidence: 99%